Reminiscing stock splits announcement: A Malaysian case - Ghazali, Zahiruddin; Md. Taib, Fauziah; Othman, Noraini (Pak Publishing Group, 2014)
This study attempts to understands and verify the effects of stock splits on the abnormal returns of announcing companies share prices using Market Adjusted Returns (MAR) Model.Test findings reveal splits announcements in Malaysia result in positive but insignificant abnormal returns. Additional OLS test was carry out to examine the relationship between companies’ cumulative abnormal returns (CAAR) and prior dividend yield (PDY). Result from uni-variate regression analysis shows there is minimal but significant positive relationship between CAAR and PDY.